Use of Electroencephalography for the Study of Gain–Loss Asymmetry in Intertemporal Decision-Making - Zhao, Lei; Shi, Zuoli; Zheng, Qian; Chu, Huadong; Xu, Lin; Hu, Fengpei (Frontiers in Neuroscience, 2018)
Intertemporal decision refers to the process whereby an individual judges and selects between multiple choices based on cost and benefit over time. Previous studies on temporal discount have focused on gain decision areas, while few studies focused on loss context. Based on this, we used event-related potential (ERP) technology and graph theory analysis to explore the differences in intertemporal decision-making under the framework of gain and loss. We found that in a loss context, the participants preferred the short latency time/small amount (SS) choices, and showed a smaller discount rate. Our ERP results indicated that the P200 component can be a preliminary assessment of the choices of gain and loss. In contrast, the N2 component is related to negative emotions and shows significantly bigger amplitude in a loss context. Further analyses of brain networks suggested that the loss decision-making brain network has larger small-worldness index due to an individual’s aversion to losses. Taken together, loss decision with more resources involved showed greater response in the brain mechanism because of the negative emotions linked to loss aversion.